2005
DOI: 10.1002/ps.1046
|View full text |Cite
|
Sign up to set email alerts
|

In vivo metabolic fate of [14C]‐acetamiprid in six biological compartments of the honeybee, Apis mellifera L

Abstract: The in vivo metabolism of acetamiprid was studied in the honeybee, Apis mellifera L. The distribution of acetamiprid and its metabolites was monitored over a 72-h period in six biological compartments: head, thorax, abdomen, haemolymph, midgut and rectum. Honeybees were treated orally with 100 microg [14C]-acetamiprid kg(-1) bee, a dose which is about 1500 times lower than the median lethal dose. After 72 h, only 40% of the total radioactivity was eliminated, suggesting that acetamiprid and its metabolites ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 38 publications
4
65
0
5
Order By: Relevance
“…However the substrate AAP was continuously reduced. In honeybee and plant, the further degradation of IM 2-1 yields the end products namely, IC-O (6-chloro-nicotinic acid) (Brunet et al 2005). However beside the product IM 2-1, no other metabolite in transformation broth was observed under UV wavelength by HPLC analysis in this study.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However the substrate AAP was continuously reduced. In honeybee and plant, the further degradation of IM 2-1 yields the end products namely, IC-O (6-chloro-nicotinic acid) (Brunet et al 2005). However beside the product IM 2-1, no other metabolite in transformation broth was observed under UV wavelength by HPLC analysis in this study.…”
Section: Discussionmentioning
confidence: 79%
“…Study on the metabolism of AAP by plant, rat and honeybee showed that, besides producing metabolites such as IM 1-2, IM 1-4, IM 1-5 and IC-0, the N-demthylation of AAP to yield IM 2-1 was the main pathway (Brunet et al 2005). However, metabolic products of AAP in soils under aerobic conditions were IM 1-4, IM 1-5 and IC-0, while the metabolic products of AAP in an aerobic sediment-water system were IM 1-2, IM 1-4 and IC-0.…”
Section: Discussionmentioning
confidence: 99%
“…Imidacloprid has an elimination half-life in honeybees of 4.5 h [32] resulting in two main metabolites, 6-chloronicotinic acid and the urea derivative. The metabolic pathway for other neonicotinoid insecticides such as acetamiprid also ends in 6-chloronicotinic acid [34]. This suggests that 6-chloronicotinic acid residues might not have originated only from exposure to imidacloprid but also from other neonicotinoid insecticides such as acetamiprid.…”
Section: Discussionmentioning
confidence: 97%
“…3A-C). [37][38][39] Hydroxylation and N-dealkylation are likely the key reactions catalyzed by A. gossypii CYP6CY22 and CYP6CY13, respectively.…”
Section: Discussionmentioning
confidence: 99%